Inovasi Pelayanan Pengaduan Hotline Di Rumah Sakit Umum Daerah Kabupaten Pangkajene Dan Kepulauan - Nurkhalisa, Nurkhalisa; Razak, Andi Rosdianti; Tahir, Muhammad (Universitas Muhammadiyah Makassar, 2021)
This study aimed to describe the Innovation of Hotline complaint services at the Pangkajene and Kepulauan Regency General Hospitals. The research method used qualitative. The number of informants in this study were 5 people. Data collection technique were observation, interviews and documentation.Data analysis used data reduction, data presentation and conclusions, while the validity of the data using source, method and time triggers. The results of this study showed that the Hotline complaint service innovation at the Pangkajene and Kepulauan Regency General Hospitals was seen from five dimensions. In accordance with previous innovations and in accordance with operational service standards, the procedure for Hotline complaint depended on human resources. The possibility of trying Hotline complaint services could improve the quality of services. Ease of observing, Hotline complaint could be quickly followed up in providing criticism and suggestions.